2022
DOI: 10.1186/s13063-022-06239-3
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Subthreshold Exercise Program (MSTEP) for concussion: study protocol for a randomized controlled trial

Abstract: Background Subthreshold exercise, defined as aerobic exercise below the level that causes symptoms, has been utilized as a treatment for youth with persistent postconcussive symptoms (PPCS), but there is currently little evidence to guide use. In addition, prior studies of exercise for PPCS have all required multiple in-person visits. We developed a virtual approach for delivering subthreshold exercise to youth with PPCS called the Mobile Subthreshold Exercise Program (MSTEP), and we have now b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…The decentralized elements used in the identified DCT cases were consistent with the patient safety and data integrity. In the identified DCT cases, most interventions showed low risk and were easy to implement [ 23 24 ]. The indications for the drug-related DCT cases were mainly chronic or prophylactic conditions that did not require urgent management [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decentralized elements used in the identified DCT cases were consistent with the patient safety and data integrity. In the identified DCT cases, most interventions showed low risk and were easy to implement [ 23 24 ]. The indications for the drug-related DCT cases were mainly chronic or prophylactic conditions that did not require urgent management [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simple lifestyle strategies such as activity and exercise can have specific positive effects on PD symptoms, thereby contributing meaningfully to the QOL of PwP in numerous ways. 6 Classical face-to-face exercise programs and regimes have been shown to reduce the burden of progressive PD symptoms, [7][8][9] improve non-motor symptoms 10 and enhance overall QOL in PwP. 11 Furthermore, exercise has been shown to confer positive effects on symptoms in newly-diagnosed PD patients, 8 and long-term studies have shown that regular activity and exercise levels can also reduce a person's lifetime risk of developing PD.…”
Section: Introductionmentioning
confidence: 99%